Application of a projective method for the assessment of children’s dental fear (Revista Nacional de Odontología, 2017)
The aims of this study were to assess children's dental fear by using a projective technique CDFP (Children’s dental fear picture test). 40 patients from a pediatric dental clinic, between 5-9 years old, took part in this study. At first, the CDFP was applied to the children. This method has three subtests and its overall assessment classifies children as "fearful, non fearful and uncertain". The children answered the CFSS-DS (Children Fear Survey Schedule–Dental Subscale). The results showed that CDFP has inter-examiner reliability and a significant correlation with the CFSS-DS was observed.
Keywords: child behavior; dental fear; pediatric dentistry; psychology